Looking for coordinates - Hochradner, Thomas (Muzikološki zbornik, 2013)
Research in reception of music usually tends to case studies or tabular forms, whereas studies in interpretation of music often are questioned with regard to the imponderabilities of technical conditions and optional revisions of sound recordings. As a lack of consciousness in respect to referential systems seems to be the starting point of the problem, the following paper suggests a basic model which is able to deal with music in all its writtenand sonorous manifestations.
Keywords: zgodovina interpretacije glasbe; zgodovina recepcije